Optical Properties of AgInS2 Quantum Dots Synthesized in a 3D-Printed Microfluidic Chip - Konstantin Baranov; Ivan Reznik; Sofia Karamysheva; Jacobus W. Swart; Stanislav Moshkalev; Anna Orlova (Technologies, 2023)
Colloidal nanoparticles, and quantum dots in particular, are a new class of materials that can significantly improve the functionality of photonics, electronics, sensor devices, etc. The main challenge addressed in the article is modification of the syntheses of colloidal NP to launch them into mass production. It is proposed to use an additive printing method of chips for microfluidic synthesis, and it is shown that our approach allows to offer a cheap, easily scalable and automated synthesis method which allows to increase the product yield up to 60% with improved optical properties of <semantics>AgInS2</semantics> quantum dots.